Identifying crop variants with high resistant starch content to maintain healthy glucose homeostasis. Issue 4 (December 2016) - Petropoulou, K.; Chambers, E. S.; Morrison, D. J.; Preston, T.; Godsland, I. F.; Wilde, P.; Narbad, A.; Parker, R.; Salt, L.; Morris, V. J.; Domoney, C.; Persaud, S. J.; et al.
Abstract: Identifying dietary tools that prevent disordered insulin secretion from pancreatic β‐cells is an attractive strategy to combat the increasing prevalence of type 2 diabetes. Dietary resistant starch has been linked to improvements in the function of β‐cells, possibly via increased colonic fermentation and production of short‐chain fatty acids (SCFAs). Increasing the resistant starch content of commonly consumed foods could therefore maintain glucose homeostasis at the population level. As part of Biotechnology and Biological Sciences Research Council (BBSRC) Diet and Health Research Industry Club (DRINC) initiative, variants of Pisum sativum L. (pea) are being investigated to identify the features of pea starch that make it resistant to digestion and available for colonic fermentation and SCFA production. Parallel in vitro and in vivo studies are being conducted using both whole pea seeds and pea flour to facilitate a better understanding of how cells in the pea cotyledons are affected by processing and, in turn, how this influences starch digestibility. Trials in human volunteers are being used to monitor a full spectrum of short‐ and long‐term physiological responses relevant to pancreatic β‐cell function and glucose homeostasis. This project is providing new insights into variants of crops that are associated with the specific types of resistant starch that provide the best protection against defects in insulin secretion and function.